The welfare costs of inflation reconsidered - Luca Benati; Juan Pablo Nicolini (University of Bern, Department of Economics, 2024)
We revisit the estimation of the welfare costs of inflation originating from lack of liquidity satiation for 11 low-inflation and 5 high-inflation countries, and for Weimar Republic's hyperinflation. Our evidence suggests that, contrary to the implicit assumption in much of the literature, these costs are far from negligible. For the U.S. our point estimates are equal to about one-third of those computed by Lucas (2000), and an order of magnitude larger than those obtained by Ireland (2009). Crucially, the most empirically plausible moneydemand functional form points towards sizeable "upward risks" for these costs, with the 90% confidence interval associated with a 4% nominal interest rate stretching beyond 0.5 per cent of GDP. The welfare costs of inflation in the Euro area are about twice as large as in the U.S., thus suggesting that, ceteris paribus, the inflation target should be materially lower. At the peak of the inflation episodes, welfare costs had ranged between 0.3 and 1.9 per cent of GDP for low-inflation countries; between 4 and nearly 7 per cent for highinflation ones; and between 26 and 36 per cent for Weimar's hyperinflation.
Keywords: 330